Impact and Law Enforcement of Vigilante in the Society - Margareta, Veronica Sherly; Waspiah, Waspiah (Universitas Negeri Semarang, 2020)
This study aims to determine: the meaning of vigilante action or eigenrechting, the impact that can be caused by vigilante action and, law enforcement against vigilante action in society. This research is included in the type of qualitative research which is a literature study (Library Research) which uses journals as reading references. The method used is descriptive analysis by providing clear, objective, systematic, analytical and critical descriptions and information regarding the impact and law enforcement of self-play in the community. The data used in this study is secondary data whose material is sourced from legal journals. The act of vigilantism is a translation of the word from the Dutch language, namely